2006
DOI: 10.1159/000097984
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Processed Water on Constitutive and Ultraviolet-A-Radiation-Induced Level of Mitochondrial DNA Mutations in Human Dermal Fibroblasts

Abstract: The integrity of the mitochondrial genome is of crucial importance for the cellular energy metabolism, and increased mutation rates are causally related to premature ageing. Wedemonstrate that replacement of normal deionized water with processed water in cell culture medium decreases the constitutive levels of the most frequent large-scale deletion of the mitochondrial genome in human dermal fibroblasts. In addition the presence of processed water also prevented the generation of the common deletion which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Morphological and histological changes of photoaged human skin have long been studied. Recent studies investigating photoaging mechanisms have focused on protein oxidative damage [1,2] , mitochondrial DNA deletion [3,4] , acceleration of decorative telomeres [5,6] , alteration of membrane/nuclear signals [7,8] , or the role of neutrophils [9] . Although the mechanisms underlying human skin photoaging have been studied extensively, the picture remains unclear, especially regarding the roles of photoaging-dependent enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological and histological changes of photoaged human skin have long been studied. Recent studies investigating photoaging mechanisms have focused on protein oxidative damage [1,2] , mitochondrial DNA deletion [3,4] , acceleration of decorative telomeres [5,6] , alteration of membrane/nuclear signals [7,8] , or the role of neutrophils [9] . Although the mechanisms underlying human skin photoaging have been studied extensively, the picture remains unclear, especially regarding the roles of photoaging-dependent enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies revealed that DNA damage and DNA repair abnormality were involved in the occurrence of chronic skin damages. [22][23][24] Repeated UV irradiation could cause multiple types of DNA damage, which was the material basis for the occurrence of light source skin tumors. 25,26 We found that LncSPRY4-IT1 was involved…”
Section: Discussionmentioning
confidence: 99%